Contralateral metachronous undescended testis: Is it predictable?. Issue 5 (October 2017) - Cancian, Madeline; Ellsworth, Pamela; Caldamone, Anthony
Summary: Introduction: Metachronous undescended testis (mcUDT), an acquired UDT after contralateral orchiopexy, can occur in some boys. If one were able to predict its occurrence, one might consider a proactive approach or at least one would be able to counsel the parents accordingly. Our hypothesis was there may be characteristics evident at the time of initial orchiopexy which could predict the development of contralateral mcUDT. Objective: The aim was to Identify factors present at initial orchiopexy that predict development of subsequent mcUDT. Study design: Subjects were identified using the Current Procedural Terminology code for inguinal orchiopexy (54640). We included patients from January 1997 to October 2015. We included patients who underwent orchiopexy for unilateral UDT (uUDT). The study population consisted of patients who had undergone metachronous orchiopexies; controls were patients who were 17 years at time of data collection with a single orchiopexy. Cox proportional hazard regression was used to model the relationship between possible predictors of subsequent UDT using PROC PHREG with SAS Software 9.4. Results: From 1035 eligible patients we identified 38 with mcUDT and 207 controls (uUDT). Median age at the first orchiopexy of mcUDT patients was 2.5 years (min/max, 0.50/10.4 years) and 8.2 years (min/max 0.70/12.8 years) for uUDT, p < 0.0001. Subjects with a contralateral retractile testis on preoperative exam had a 4.2 times higher rate of subsequent UDT than patients with a contralateral descended testis (95% CI 2.077–8.353). The rate of mcUDT was 6.7 times higher if the testis was a retractile testis under anesthesia (95% CI 2.7–16.5) (Table). Discussion: Contralateral retractile UDT was a significant predictor of mcUDT. We believe patients with a contralateral retractile testis at time of orchiopexy should be counseled on bilateral orchiopexy. The risks of complications with orchiopexy should be weighed against risks of a subsequent surgery and anesthesia event. Conclusion: A discussion of risks and benefits regarding bilateral orchiopexies should be undertaken with the parents prior to surgery in the setting of an UDT with contralateral retractile testis. Table Patient characteristics and predictors of mcUDT. Contralateral UDT (38) Unilateral UDT (204) p Age at initial orchiopexy, years 2.5 8.2 <0.0001 Congenital, % 65 52 0.10 Contralateral examination in office (% retractile) 52 18 <0.0001 Contralateral examination under anesthesia (% retractile) 22 2 <0.0001 Ipsilateral PV open, % 48 59 0.14 PV = processus vaginalis.